(untitled) (TAJ: Journal of Teachers Association, 2023)
Introduction: Though the health situation of Bangladesh has been improved substantially over the years, the low birth weight (LBW) rate is still pretty high. LBW has been associated with high probability of infection, malnutrition, mental deficiencies and behavioural and learning problem in later life. The principle focus of this study was to ascertain the proportion of LBW and its associated maternal risk factors identification. Materials & methods: It was a cross-sectional type of descriptive study done at two tertiary level hospitals – Rajshahi Medical College Hospital and Islami Bank Medical College Hospital. A total of 270 mothers were interviewed within 1 month of their delivery. The purposively selected participants were asked about their socio-demographic characters and other associated factors related to birth of the babies. Weights of the babies at birth were documented from hospital records. Result: Proportion of LBW was found 28.1% with no significant sex variation. Majority of the LBW babies were found in mothers of 15-20 years of age group. Mothers’ educational qualifications, occupations, early age pregnancy and type of pregnancy were associated significantly for LBW. Less than 37 weeks of gestational age of baby, home delivery, NVD were also significant risk factors of LBW. Residence and sex of neonate were not significantly associated with LBW. Conclusion: Proportion of LBW in tertiary care hospitals were found 28.1%. Early maternal pregnancy, lower gestational age, higher parity, NVD and home delivery played an important role in the incidence of LBW. TAJ 2023; 36: No-2: 207-214